2023
DOI: 10.1002/cpt.2828
|View full text |Cite
|
Sign up to set email alerts
|

Safety Monitoring of COVID‐19 Vaccines: Perspective from the European Medicines Agency

Abstract: Prior to deployment of COVID‐19 vaccines in the European Union (EU) in 2021, a high vaccine uptake leading to an unprecedented volume of safety data from spontaneous reports and real‐world evidence, was anticipated. The European Medicines Agency (EMA) implemented specific activities to ensure enhanced monitoring of emerging vaccine safety information, including intensive monitoring of reports of adverse events of special interest (AESIs) and the use of observed‐to‐expected (O/E) analyses. EMA also commissioned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…The safety profile of COVID-19 vaccines is under continuous evaluation, with the vast majority of known adverse effects following immunization (AEFI) being minor and self-limiting [ 9 , 10 , 11 ]. Indeed, the investigation of adverse effects following immunization (AEFI) is key to monitoring the safety of vaccination series and acceptance of repeated doses in general and in specific populations [ 12 , 13 , 14 ]. Understanding AEFI predictors after COVID-19 vaccines gives the opportunity to better design prevention strategies and encourage trust building in vaccination campaigns against COVID-19 [ 2 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The safety profile of COVID-19 vaccines is under continuous evaluation, with the vast majority of known adverse effects following immunization (AEFI) being minor and self-limiting [ 9 , 10 , 11 ]. Indeed, the investigation of adverse effects following immunization (AEFI) is key to monitoring the safety of vaccination series and acceptance of repeated doses in general and in specific populations [ 12 , 13 , 14 ]. Understanding AEFI predictors after COVID-19 vaccines gives the opportunity to better design prevention strategies and encourage trust building in vaccination campaigns against COVID-19 [ 2 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Charles Khouri 1,2, * , Michele Fusaroli 3 , Francesco Salvo 4,5 and Emanuel Raschi 3 We read with interest the study by Prontskus and colleagues, 1 which analyzed the French and the World Health Organization (WHO) spontaneous reporting systems to investigate the potential link between coronavirus disease 2019 (COVID-19) vaccination and rheumatic arthritis onset and flares. The research question and its implications are important.…”
Section: Interpretation Of Pharmacovigilance Disproportionality Analysesmentioning
confidence: 99%
“…In the field of vaccine safety, pharmacoepidemiological studies using healthcare databases, active intense monitoring, and observed-to-expected analyses are warranted to support signal assessment, relevant contextualization, and communication. 3 Previous meta-epidemiological studies have shown common misinterpretation (also called spin) of results from disproportionality analyses in published studies. 2 Many disproportionality analyses intentionally or unintentionally overstate the strength of causal links, lack proper handling and discussion of biases, or over-extrapolate results to provide clinical recommendations or compare drug safety profiles.…”
Section: Interpretation Of Pharmacovigilance Disproportionality Analysesmentioning
confidence: 99%
“…Regular updates of the AESI list, including used case definitions (e.g., Brighton collaboration), remain necessary. Unfortunately, for safety signals dealing with unexpected events, the assessments had to deal with more uncertainties and a lack of accurate background incidence rates adequately stratified by age and geographical regions [ 17 ].…”
Section: Investigating Pharmacovigilance Databasesmentioning
confidence: 99%